Anti‐hyperglycemic and anti‐hyperlipidemic effects of Vaccinium myrtillus fruit in experimentally induced diabetes (antidiabetic effect of Vaccinium myrtillus fruit). (19th March 2015) - Asgary, Sedigheh; RafieianKopaei, Mahmood; Sahebkar, Amirhossein; Shamsi, Fatemeh; Goli‐malekabadi, Najmeh
Abstract: BACKGROUND: Diabetes mellitus (DM) is a metabolic disorder that is associated with an increased risk of cardiovascular disease. Vaccinium myrtillus (bilberry) is a useful plant with antidiabetic properties in traditional medicine. The aim of this study was to investigate the effects of bilberry against DM. Diabetes was induced using intraperitoneal injection of alloxan (120 mg kg −1 body weight (BW)). Bilberry powder (2 g d −1 ) and glibenclamide (positive control; 0.6 mg kg −1 BW) were administered for 4 weeks following alloxan injection. Serum glucose, insulin, total cholesterol (TC), low‐density lipoprotein cholesterol (LDL‐C), high‐density lipoprotein cholesterol (HDL‐C), very‐low‐density lipoprotein cholesterol (VLDL‐C), triglycerides (TG) and C‐reactive protein (CRP) were determined at baseline and at 2nd and 4th week of the study. RESULTS: Bilberry supplementation resulted in a significant reduction of glucose compared with the diabetic control as well as glibenclamide treatment. Bilberry elevated insulin, reduced TC, LDL‐C, VLDL‐C and TG levels, and prevented HDL‐C decline. Serum insulin, TC and LDL‐C levels were not affected by glibenclamide, and CRP did not significantly change with either bilberry or glibenclamide. Histological examinations revealed a significant elevation of islet size in the bilberry and glibenclamide‐treated groups. CONCLUSION: Dietary supplementation with bilberry fruits may protect against impaired glucose and lipid metabolism in DM. © 2015 Society of Chemical Industry